Characterization of Salivary Metabolic Profiles in Early Childhood Caries (ECC): Diagnostic, Preventive and Therapeutic Implications - Pereira, Joana Leonor Sousa Almeida (2020)
Tese de Doutoramento em Ciências da Saúde, ramo de Medicina Dentária, apresentada à Faculdade de Medicina da Universidade de Coimbra